Mapping Two Decades of Conflict Resolution Research: A Scopus-Based Bibliometric Study - Shopyan Jepri Kurniawan; Bambang Dibyo Wiyono; Budi Purwoko; Mohd. Aziz Zulazmi (Universitas Negeri Padang, 2026)
This study offers a systematic bibliometric analysis of global conflict resolution research published between 2000 and 2025. Its aim is to identify publication trends, leading countries and institutions, influential authors, productive journals, and thematic developments within the field, serving as guidance for studies in guidance and counselling. Using the PRISMA protocol, data were solely retrieved from the Scopus database, limited to peer-reviewed English-language journal articles. The final dataset was analysed using VOSviewer to map co-authorship networks, institutional collaborations, citation patterns, and keyword co-occurrence. The results reveal a steady increase in the number of conflict resolution publications, with the most significant growth occurring from 2020 to 2025. The United States emerged as the most prolific contributor, followed by Germany, the United Kingdom, Canada, China, and Spain. Leading institutions such as the University of California, Utrecht University, Southwest University, Tel Aviv University, and Beijing Normal University demonstrate strong collaborative activity. Thematic mapping indicates a sustained research focus on interpersonal conflict, emotion regulation, communication, and peace education. This study provides a comprehensive overview of the structure and evolution of conflict resolution research and highlights opportunities for future investigation, particularly in education and counselling.